Regional development in Amazonas, Peru: science-society interactions for sustainability - Mick, Carola; Fernández, María E.; Alvarado Chuqui, Cástula; Amasifuen Guerra, Carlos Alberto; Kleiche Dray, Mina; López Minchán, Ana Paula; Silva López, Jhonsy Omar (SAGE Journals, 2020)
Scientific-technological knowledge maintains the anthropocentric power-pattern and exploitive attitude with regard to nature, but sustainability science asks for an integration of territorial and decontextualized knowledge systems. Visual participatory methodologies involving diverse local stakeholder facilitate dialogue on environmental and sustainability issues. Inspired by visual ethnography and mediated discourse analysis, the present article uses semiological analysis to reconstruct the depicted narratives on the nature-society system in drawings representing “regional development”. The drawings were elaborated in a series of participatory workshops involving university faculty and students, regional government and non-governmental organizations and farmers from local communities in the northern Amazonian region of Peru. The analysis reveals a prevailing anthropo and technology centered, “colonial” conception of the nature-society system, and a marginalization of alternative narratives. Beyond confirming the potential for visual participatory methods to enhance multi-stakeholder dialogue, it demonstrates how semiological analysis can be used to deepen an understanding of the cultural, organizational and technological constraints facing critical, trans-disciplinary efforts to decolonize the technology-centered, anthropocentric mainstream worldview of nature and society.